Towards a universal optimization of the performance of sand storage dams in arid and semi-arid areas by systematically minimizing vulnerability to siltation : a case study in Makueni, Kenya - Josep de Trincheria and Walter Leal Filho and Ralf Otterpohl (International Journal of Sediment Research, 2018)
Sand storage dams are hydraulic retention structures that increase the volume of coarse sediments in seasonal sandy streams by exclusively blocking the bedload transport during runoff events. However, siltation of fine grain particles, which are transported as part of the suspended load, is a major factor causing sand storage dams to perform poorly. Therefore, this study aimed to evaluate the hydrological performance and cost-efficiency of 30 sand storage dams. This study also aimed to increase the understanding of critical factors which may affect the performance and lead to siltation of sand storage reservoirs. The analysis was based on a physical survey of 30 sand storage dams that were built in one-stage in southeastern Kenya. Most of the study sites had the capacity to produce sand. However, the reservoirs suffered from severe siltation, which caused generalized low annual yields, reduced supply capacities, and low cost-efficiency. It is argued that the main factors for the poor performance were the high inter- and intra-annual variability of bedload transport, which coupled with the construction of one-stage spillways, led to siltation of the reservoirs. Thus, large volumes of fine grain particles accumulated in the reservoirs during runoff events with bedload layer heights lower than the height of the one-stage spillways. To systematically maximize the robustness to the inherent variability of bedload transport, and ensure optimal performance levels by systematically minimizing siltation, spillways should be built in stages of reduced height. Thus, the lower the stage height, the higher the probability of maximizing the accumulation of coarse sediment. It is estimated that a multi-stage construction process with stage heights of 20?cm would have produced a performance 26 times higher. This implies that the 30 reservoirs would have had the capacity to supply 8516 people as compared to the current supply capacity of 330 people. Improvements in the performance of sand storage dams can greatly assist attempts to link this technology with income-generating activities for agropastoralists in arid and semi-arid areas.